Analysis Of Rhodamine B Dye Content In Lipstick At Beriman Tomohon Market - Friska M. Montolalu; Christien Kiroh; Wilmar Maarisit; Jabes W. Kanter; Andry Natanel; Amal R. Ginting; Rachmat Santoso (FMIPA UKIT, 2025)
The use of cosmetics such as lipstick aims to improve the natural appearance of the lips and induce discoloration. A problem that is often worrying about today is the presence of prohibited dyes in lipstick preparations' main components. Rhodamine B is a synthetic dye prohibited in cosmetics, especially lipsticks. This research aims to analyze the Rhodamine B dye in lipsticks that do not have a distribution permit from BPOM circulating in the Beriman Tomohon market.The research method was Thin Layer Chromatography (TLC), followed by wavelength measurement on UV-Vis Spectrophotometry. The research population was all red lipstick preparations and 10 (ten) different lipsticks as a sample.Data analysis in this research is to find the RF value obtained from TLC then make a graph of the equation y = bx + a then look for the x value to measure the Rhodamine B content in lipstick. The results of this research were obtained from 1 (one) sample of lipstick label L(I) positive containing Rhodamine B. Visually, the lipstick of the L(I) label has a pink color and fluorescence orange when irradiated with 366nm UV, Rhodamine B has an Rf value of 0.85. In contrast, the L(I) sample has an Rf value of 0.84. Rhodamine B has a wavelength of 544nm, and the lipstick sample L(I) has an absorbance of 0.362 which has a Rhodamine B content of 0.4115%.